One Health Approach for Reporting Veterinary Carbapenem-Resistant Enterobacterales and Other Bacteria of Public Health Concern - Kate KuKanich; Amy Burklund; Rob McGaughey; Nancy Muturi; Sasha Thomason; M.M. Chengappa; Ingrid Garrison; Bryna Stacey; Shuping Zhang; Tamara Gull (Emerging Infectious Diseases, 2023)
A carbapenem-resistant Enterobacterales outbreak at a veterinary teaching hospital in the United States increased urgency for improved communication among diagnostic laboratories, public health authorities, veterinarians, and pet owners. Kansas State University, University of Missouri, Kansas Department of Health and Environment, and Veterinary Laboratory Investigation and Response Network created a surveillance, storage, and reporting protocol for veterinary antimicrobial-resistant bacteria; determined frequency of those bacteria in companion animals during 2018–2021; and created educational flyers for veterinarians and pet owners. We recommend a One Health strategy to create efficient surveillance programs to identify and report antimicrobial-resistant bacteria and educate veterinarians and pet owners about transmission risks.